1978
DOI: 10.1107/s0567740878005038
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structures of hexahalouranates. I. Bis(triphenylethylphosphonium) hexachlorouranate(IV) and bis(triphenylethylphosphonium) hexabromouranate(IV)

Abstract: The crystal structures of the bis(triphenylethylphosphonium) hexahalouranates(IV), [P(C 6H5)3 C 2H5 ] 2[U X 6] IX = (I) chlorine, (II) bromine], have been determined from three-dimensional X-ray diffraction data collected on an automatic Philips PW 1100 four-circle diffractometer using 2894 (I) and 1448 (II) structure amplitudes from independent reflexions. The compounds crystallize in the (I) triclinic P i, and (II) mono-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…The Br-U-Br angles in the octahedron-like polyhedron range from 86.519 (13) to 94.879 14and show a quite significant distortion from the ideal angle of 90 . These atomic distances and angles are in good agreement with the compounds reported previously (Bohrer et al, 1988;Caira et al, 1978). The atomic distances of the two symmetry-independent triethylammonium cations are in good agreement with each other, as well as with the literature, for example in bis(triethylammonium) tetrachloridodioxidouranium(VI) (Gatto et al, 2003;Serezhkina et al, 2010;Bois et al, 1976).…”
Section: Structural Commentarysupporting
confidence: 90%
See 2 more Smart Citations
“…The Br-U-Br angles in the octahedron-like polyhedron range from 86.519 (13) to 94.879 14and show a quite significant distortion from the ideal angle of 90 . These atomic distances and angles are in good agreement with the compounds reported previously (Bohrer et al, 1988;Caira et al, 1978). The atomic distances of the two symmetry-independent triethylammonium cations are in good agreement with each other, as well as with the literature, for example in bis(triethylammonium) tetrachloridodioxidouranium(VI) (Gatto et al, 2003;Serezhkina et al, 2010;Bois et al, 1976).…”
Section: Structural Commentarysupporting
confidence: 90%
“…All these compounds have a slightly distorted octahedron-shaped [UCl 6 ] 2coordination polyhedron in common with Cl-U-Cl angles close to 90 and some of them, like [BuMeIm] 2 [UCl 6 ], feature hydrogenbonding networks or weak hydrogen interactions (Nikitenko et al, 2007). Examples of hexabromidouranates(IV) with organic cations are (PPh 4 ) 2 [UBr 6 ]Á4CH 3 CN (Bohrer et al, 1988), [P(C 6 H 5 ) 3 C 2 H 5 ] 2 [UBr 6 ] (Caira et al, 1978) or (Ph 3 Et-P) 2 [UBr 6 ] (Caira et al, 1978). As in the case of the hexachloridouranates(IV), the [UBr 6 ] 2octahedra show a slight distortion and the compounds feature an extended network of hydrogen bonds.…”
Section: Chemical Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…U-CI 2.813(4) 8, in the seven-co-ordinate [UIv-C1(OPMe3),l3+ and 2.70(2) 8, in eight-co-ordinate [UIV-C12(OSMe2),J2 + ,' although the distance is common enough in six-co-ordinate uranium(rv). 8 The mean U-0 distance of 2.35…”
Section: Discussionmentioning
confidence: 99%
“…In published structures containing ethyltriphenylphosphonium cations (Broder et al, 2002;Caira et al, 1978;Be  langer & Beauchamp, 1993;Fedin et al, 1990;Janickis et al, 2002;Ansari et al, 1990), two possible cation geometries have been observed. The criterion is the deviation of the ethyl group from the plane de®ned by the phenyl ring trans to the methyl group.…”
Section: Commentmentioning
confidence: 99%